Una mirada desde la psicología a la película “La ballena” - Camacho, Javier (2023)
Ponentes: DR. Javier Camacho (ARGENTINA); MG. Daniela Brahim (PERÚ); MG. María José Verdejo (PERÚ) / Moderadora: Dra. Natalia Torres Vilar (PERÚ)